Human Rights and the Era of Generative Artificial Intelligence – Assessing and Enhancing Pakistan’s National AI Policy with an Insight into Global Perspectives - Hina Qayyum; Mehr Un Nisa; Shizza Khan (Law and Policy Review, 2025)
This research explores the complex interplay between Generative Artificial Intelligence (GAI) and human rights. It starts by defining GAI and establishing the intrinsic importance of human rights protection in the face of such technological advancements. On one hand, it explores the potential positive effects, including improved healthcare outcomes, reduced discrimination, and increased access to education. On the other hand, it critically examines the negative consequences, such as privacy concerns arising from data collection and use, and the potential for bias and discrimination set within algorithms. To substantiate these theoretical explorations, the paper incorporates two compelling case studies: the controversial use of AI in hiring practices and predictive policing in the United States. These instances provide concrete illustrations of how GAI interacts with human rights in varied contexts. The focus is next shifted to the legal framework developed by the United States of America, the European Union, China, and Pakistan for the deployment of GAI and their relevant scopes. Pakistan’s National AI policy primarily focuses on the ways through which GAI can be used, while delaying ethical considerations, and human rights concerns. Informed by these analyses, the study recommends modifying the National AI policy of Pakistan and enacting it as soon as possible to mitigate the negative effects of GAI and maximise its potential to benefit Pakistan and humanity. This research employs a doctrinal research methodology.